Effect of thymoquinone on high fat diet and STZ‐induced experimental type 2 diabetes: A mechanistic insight by in vivo and in silico studies. Issue 8 (21st June 2021) - Alshahrani, Saeed; Anwer, Tarique; Alam, Mohammad Firoz; Ahmed, Rayan A.; Khan, Gyas; Sivakumar, Sivagurunathan Moni; Shoaib, Ambreen; Alam, Prawez; Azam, Faizul
Abstract: The aim was to investigate whether thymoquinone (TQ) attenuates hyperglycemia‐induced insulin resistance in experimental type 2 diabetes. Type 2 diabetes mellitus (T2DM) was induced by injection of streptozotocin (STZ, 40 mg/kg) in high fat diet (HFD) rats. The levels of glucose, insulin, area under curve (AUC) of glucose, lipid profile parameters, homeostasis model assessment of insulin resistance (HOMA‐IR), peroxisome proliferator‐activated receptor‐γ (PPARγ), and dipeptidyl peptidase peptidase‐IV (DPP‐IV) were evaluated in HFD + STZ‐induced type 2 diabetic rats. TQ treatment significantly reduced elevated levels of glucose, AUC of glucose, insulin, and DPP‐IV in diabetic‐treated groups. In addition, TQ treatment significantly reduced high levels of triglycerides (TG) and cholesterols (total, low‐density and very low‐density lipoprotein) accompanied by significant augmentation in high‐density lipoprotein (HDL) levels in diabetic‐treated groups. However, TQ treatment significantly improved insulin sensitivity in diabetic‐treated groups, which was confirmed by increased level of PPARγ and decreased level of HOMA‐IR. Molecular docking of TQ exhibited substantial binding affinity with PPARγ and DPP‐IV target proteins, which is supported by in vivo results. These results demonstrate that TQ attenuates hyperglycemia‐induced insulin resistance by counteracting hyperinsulinemia, improving lipid profile, insulin sensitivity, and inhibiting DPP‐IV. Practical applications: T2DM results in relentless hyperglycemia which eventually progress to a state of insulin resistance. TQ is an active principle compound found in Nigella sative seed, having myriad of traditional medicinal values. Administration of TQ significantly prevented hyperglycemia, hyperinsulinemia, hyperlipidemia, insulin resistance, and inhibited DPP‐IV in experimental type 2 diabetes. The in vivo results are also supported by molecular docking study of PPARγ and DPP‐IV target proteins. Thus, we hypothesize that TQ can be used as an alternative natural drug in the management of hyperglycemia‐induced insulin resistance in T2DM. Abstract : The administration of TQ significantly reduced elevated levels of glucose, area under curve (AUC) of glucose, insulin and dipeptidyl peptidase IV (DPP‐IV) in diabetic treated groups. In addition, TQ treatment demonstrated improvement in lipid profile and insulin sensitivity parameters in diabetic treated groups. Molecular docking study of TQ exhibited substantial binding affinity with PPARγ and DPP‐IV target proteins. These results demonstrate that TQ attenuates hyperglycemia induced insulin resistance by counteracting hyperinsulinemia, improving lipid profile, insulin sensitivity and inhibiting DPP‐IV.